Guillain-Barre Syndrome Outcome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The prognostic indicators and outcome in 297 patients with Guillain-Barre syndrome were analysed at the Istituto di Ricerche Farmacologiche 'Mario Negri', Milan, Italy.